FORMATION OF PEDAGOGICAL CULTURE COMMUNICATION BY DIALOGICAL MEANS LEARNING SITUATIONS - А.V. Lysevych (Academy of Cognitive and Natural Sciences, 2022)
The article considers the problem of formation of the Culture of pedagogic Intercourse, reveals the recessity of making up. the dialogue training situations, and shows the positive dynamics of the levels of the culture of pedagogic intercourse.